(untitled) (Colombia Medica, 1993)
Among the anxiety disorders, panic disorder represents one of the most severe and difficult psychiatric conditions to treat. This disorder is characterized by the sudden appearance of anxiety attacks that may last from I O to 30 minutes. These attacks are, in turn, characterized by the presence of at least 4 of 13 symptoms, being the most prominent fear of going mad, losing control, or fear of impending doom. As a result, approximately 10% of these patients have their first contact with the help care system in the emergency room, with the cardiologist, or internist. Thus, the purpose of the present paper is to familiarize the medical community with the major advances that have taken place in the conceptualization and treatment of this disorder over the last decade. The present paper reviews some of these advances with particular emphasis on the psychological conceptualization and treatment procedures derived from the psychobiological model of anxiety and panic developed by David Barlow because this model is less known to the medical! community. Based on the available empírica] evidence derived from recent controlled clínica! t.rials, it is concluded that psychological methods, mainly cognitive behavioral interventions, are preferred over pharmacological approaches in the treatment of this disorder. This conclusion is based on the fact that cognitive behavioral interventions produce a higher proportion of panic-free patients and that these patients show much lower relapse rates than those patients treated with pharmacological agents, especially alprazolam. Moreover, patients who received the former type of treatment learn important skills that can help them prevent and/or manage panic attacks in the future. Nonetheless, the pharmacological approach can be a great adjunctive treatment in those cases in which the clinical picture presented by the patient is very severe and/or he/she prefers a pharmacological approach over a psychological intervention.